Genetic, physiological, and cellular heterogeneities of bacterial pathogens in food matrices: Consequences for food safety. Issue 5 (26th August 2022) - Martin, Cédric Saint; Jubelin, Grégory; Darsonval, Maud; Leroy, Sabine; Leneveu‐Jenvrin, Charlène; Hmidene, Ghaya; Omhover, Lysiane; Stahl, Valérie; Guillier, Laurent; Briandet, Romain; Desvaux, Mickaël; Dubois‐Brissonnet, Florence
Abstract: In complex food systems, bacteria live in heterogeneous microstructures, and the population displays phenotypic heterogeneities at the single‐cell level. This review provides an overview of spatiotemporal drivers of phenotypic heterogeneity of bacterial pathogens in food matrices at three levels. The first level is the genotypic heterogeneity due to the possibility for various strains of a given species to contaminate food, each of them having specific genetic features. Then, physiological heterogeneities are induced within the same strain, due to specific microenvironments and heterogeneous adaptative responses to the food microstructure. The third level of phenotypic heterogeneity is related to cellular heterogeneity of the same strain in a specific microenvironment. Finally, we consider how these phenotypic heterogeneities at the single‐cell level could be implemented in mathematical models to predict bacterial behavior and help ensure microbiological food safety.